Physiological Responses of Bali Cattle with Oil Palm Integrated Farming System Based on Microclimate Environment Condition - Aditia, E. L.; Yani, A.; Fatonah, A. F. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2017)
Microclimate is one factor that can affect the performance of cattle. The aim of this research was to analyze the physiological responses of bali cow and heifer that kept under oil palm integrated farming system based on microclimate environment. This study was conducted in Rimba Beringin, Tapung Hulu, Kampar, Riau. Total 13 head of female Bali cattle consist of 5 head of heifer and 8 head of cow were used in the research. Microclimate parameters were ambient temperature, relative humidity, wind velocity. Whereas, physiological responses parameters were rectal temperature, heart rate, respiration rate, and body surface temperature. The result showed that Bali cattle has mild to severe heat stress (THI 76-84). However physiological responses of Bali cattle were normal, therefore Bali cattle can adaptated in the environment. Orbital area, top of shoulder and back have coefficent of correlation 0.58, 0.46, dan 0.45 repectively with the rectal temperature.